Improving Parenting Self-Efficacy in Post-Partum Sectio Caesarea - Azizah, Nurul; Rosyidah, Rafhani; Jayanti, Ratna Dwi (Universitas Islam Lamongan, 2022)
Postpartum cesarean will undergo many physiological changes. In this phase, mothers often become more sensitive due to various changes that occur both physically and emotionally, thus requiring an adjustment or adaptation process for the mother. Parenting Self Efficacy is an effort to foster parental confidence in their ability to manage and carry out caring for the baby, including post-C-section delivery.The research design used a quasi-experimental method through pre and post-test with a control group non-probability sampling technique with a purposive sampling approach. The research subjects were 30 postpartum cesareans and were divided into experimental and control groups. The intervention group was given booklets and counseling, while the control group was only given booklets. Data collection using the PSE Scale instrument and family support instruments. Data analysis used an independent sample t-test. This research was conducted at Siti Fatimah Hospital, Tulangan Sidoarjo. The research population is all postpartum cesarean mothers. The sample of this research was 30 postpartum mothers (6 hours-1 per day) wreathed at Siti Fatimah Hospital, Tulangan Sidoarjo.The results of the study After being given the booklet and counseling, there was a significant increase in the intervention group. There were differences in PSE scores on cognitive aspects, affective aspects, skills aspects, and parenting self-efficacy, the characteristics of the research subjects in the intervention and control groups were homogeneous, and most of the intervention groups had scores which were as higher 9 (60%) after the intervention was given significantly (p<0.05). Suggestions for providing PSE information through counseling and providing booklets in hospitals by midwives can be given to all postpartum, especially new parents, individually to provide knowledge and self-confidence for mothers in caring for themselves and their babies at home.